CAR-T Cell Therapy: Illuminating the Path to Solid Tumour Recovery - Karati, Dipanjan; Sarkar, Sinjini; Kundu, Moumita; Majumder, Pratyasha; Biswas, Aishi; Mondal, Tarishi; Bandyopadhyay, Soumendra Nath; Mahanti, Beduin; Mukherjee, Swarupananda (Current Cell Science, 2025)
The favourable results of Chimeric Antigen Receptor (CAR) T-cell therapy in the management of hematologic malignancies have heightened the formerly unparalleled enthusiasm for employing this novel strategy in the treatment of diverse types of human malignancies. Although there has been a lot of study on increasing the effectiveness of these cells in solid tumors, few studies have examined challenges and potential fixes. A number of the main challenges that CAR-T-cells face include confined trafficking and penetration into the tumour zone, hypoxic and immunosuppressive tumour microenvironment (TME), antigen escape and heterogeneity, CAR-T-cell fatigue, and intense incurable toxicities. Beyond these constraints, CAR designs must expand their applicability to a wider variety of malignancies by surpassing the standard architectures. In order to overcome current obstacles and improve the efficacy and materiality of this therapeutic manner, investigators are combining many medicinal approaches with a broad range of engineering solutions.
Keywords: CAR-T cell therapy